Obstacles to educational planning in public schools in Madaba Governorate, Jordan, from the point of view of school principals and principals during the (Covid-19) pandemic - Abu Shannar, Raja'i Ahmad Muhammad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of obstacles to educational planning in public schools in Madaba Governorate, Jordan, from the point of view of school principals during the (Covid-19) pandemic. The researcher used the descriptive analytical method, and the study sample consisted of (77) male and female principals of public schools. ), where the field of relationship with the local community ranked first with an arithmetic average (4.02) with a high degree, and the field of material capabilities ranked second with an arithmetic average (3.96) with a high degree, and the field of teachers ranked third with an arithmetic average (3.28) with a medium degree, and the administrative field came in the rank The fourth with an arithmetic average (3.27) with a medium degree, the teachers’ domain came third with an arithmetic average (3.28) with a medium degree, the administrative field came fourth with an arithmetic average (3.27) with a medium degree, and the students’ field came in the fifth rank with an arithmetic average (3.20) with a medium degree, and in light of Results The researcher concluded a set of recommendations and proposals to overcome the obstacles and limit their effects in the Madaba Governorate and the general schools of the Kingdom of Jordan, such as providing material and moral capabilities to the leaders in the institution. Educational institutions, the need for an educational supervisory body in educational institutions, the need to communicate with the local community and the exchange of participation in developing educational plans, and the need to strengthen the partnership between teachers and school administration.
Keywords: Educational obstacles; educational planning; school administration; COVID-19